2013
DOI: 10.4236/jbise.2013.69112
|View full text |Cite
|
Sign up to set email alerts
|

Aortic endovascular repair modeling using the finite element method

Abstract: Aim: The goal is to simulate different stages of the endovascular procedure in the preoperative phase. Methods: We have developed a numerical model of the endovascular treatment of abdominal aortic aneurysms (AAA) using finite element analysis (FEA), we took into account the geometry of the biological region reconstructed from scans, a local characterization of the guidewire/catheter mechanical properties, a mapping of material properties depending on the degree of calcification, a real behavior of the vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…However, the published results were compared with only 2D intraoperative data, and the implicit method used showed convergence difficulties when facing tortuous anatomies. Finally, Mouktadiri et al showed the feasibility of the use of the explicit finite element method in the simulation of the insertion of endovascular devices; however, no extra‐stiff guidewires were modeled and no quantitative information regarding comparisons with intraoperative data was presented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the published results were compared with only 2D intraoperative data, and the implicit method used showed convergence difficulties when facing tortuous anatomies. Finally, Mouktadiri et al showed the feasibility of the use of the explicit finite element method in the simulation of the insertion of endovascular devices; however, no extra‐stiff guidewires were modeled and no quantitative information regarding comparisons with intraoperative data was presented.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation is presented on a patient‐specific case involving a complex anatomy in order to prove the feasibility of the method, and the results are compared with 3D imaging data acquired during the surgical procedure. The support provided by surrounding organs and bones structures is taken into account in a more realistic way than what was proposed in previous publications . As very few clinical or experimental data are available concerning this particular aspect, we carried out a sensitivity study to understand the effect of the parameters introduced to model the external support.…”
Section: Introductionmentioning
confidence: 99%
“…Another fast-developing strategy to resolve the mismatch between the real-time anatomy and the image fusion roadmap, is the use of deformable (dynamic) image fusion applications (18)(19)(20)(21). These applications generate a deformable model of the vascular geometry, in which the distance between certain subsections can be modified or stretched to allow dynamic corrections to match with the real-time anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…The guide is inserted at a constant speed and angle and the model calculates the dynamic deformation of the aorta at the passage of the guide as well as the stress distribution in the structure. More details are available in [6]. Figure 8 shows the deformations caused by the insertion of different guides as well as the stress distribution in the aorta.…”
Section: B Numerical Simulation Of An Evarmentioning
confidence: 99%